1998
DOI: 10.1021/bp980071q
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Recombinant Ovine Growth Hormone with Retention of Native-like Secondary Structure and Its Refolding from the Inclusion Bodies of Escherichia coli

Abstract: Ovine growth hormone was expressed in Escherichia coli in the form of inclusion bodies using the pQE-30 expression vector. In a simple fed-batch fermentation, 800 mg/L of recombinant ovine growth hormone (r-oGH) was produced at a cell concentration of 12 g dry cell weight/L. Inclusion bodies were isolated from cells with >95% purity by extensive washing using detergent, and the r-oGH from the purified inclusion bodies was solubilized in 2 M Tris-HCl buffer at pH 12 containing 2 M urea. The r-oGH solubilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 35 publications
1
65
0
1
Order By: Relevance
“…Inclusion bodies purified as described above were resuspended in IB denaturation buffer (100 mM Tris [pH 12.0], 2 M urea), conditions that unfolded the proteins only partially, allowing effective renaturation (35). To avoid precipitation of the Mod proteins, the concentration of the proteins was adjusted to 1 mg/ml and the sample was transferred to a dialysis bag (type 20 dialysis membrane; Biomol, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion bodies purified as described above were resuspended in IB denaturation buffer (100 mM Tris [pH 12.0], 2 M urea), conditions that unfolded the proteins only partially, allowing effective renaturation (35). To avoid precipitation of the Mod proteins, the concentration of the proteins was adjusted to 1 mg/ml and the sample was transferred to a dialysis bag (type 20 dialysis membrane; Biomol, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] It has also been found that the solubilization of r-hGH inclusion bodies at alkaline pH in the presence of 2 M urea solution was more efficient than at alkaline pH only. This method resulted in about 94% of solubility, and the overall yield of the purified r-hGH was about 50% of the initial inclusion body proteins.…”
Section: Solubilization Of R-hghmentioning
confidence: 97%
“…DISCUSSION We used size-exclusion chromatography to fold the ␤ 1b -subunit from voltage-activated calcium channels into active monomers. The ␤ 1b -subunit with 65 kDa is the largest protein so far refolded by this method that was initially applied to fold smaller proteins with molecular masses between 14 -20 kDa (17,22,23). The successful use of this method for the ␤ 1b -subunit might be associated to its multi-domain structure (11) and, whether the SEC-based refolding procedure can be generally applied to larger proteins lacking such a feature, can not be anticipated from this work.…”
Section: Effect Of the Folded-␤ 1b On ␣ 1c -Calcium Channels Expressementioning
confidence: 98%